Evaluation of facial cleanliness and environmental improvement activities: Lessons learned from Malawi, Tanzania, and Uganda. - Angelia M Sanders; Ruth Dixon; Logan Stuck; Michaela Kelly; Geordie Woods; Edridah M Muheki; Gilbert Baayenda; Michael Masika; Holystone Kafanikhale; Upendo Mwingira; Leah Wohlgemuth (Public Library of Science (PLoS), 2021)
The World Health Organization promotes the SAFE (Surgery, Antibiotics, Facial cleanliness, and Environmental improvements) strategy for trachoma control and prevention. The F&E components of the strategy focus on promotion of healthy hygiene and sanitation behaviors. In order to monitor F&E activities implemented across villages and schools in Malawi, Tanzania, and Uganda, an F&E Monitoring and Evaluation (FEME) framework was developed to track quarterly program outputs and to provide the basis for a pre and post evaluation of the activities. Results showed an increase in knowledge at the school and household levels, and in some cases, an increase in presence of hand/face washing stations. However, this did not always result in a change in trachoma prevention behaviors such as facial cleanliness or keeping compounds free of human feces. The results highlight that the F&E programs were effective in increasing awareness of trachoma prevention but not able to translate that knowledge into changes in behavior during the time between pre and post-surveys. This study also indicates the potential to improve the data collection and survey design and notes that the period of intervention was not long enough to measure significant changes.